Systematic evaluation of olfaction in patients with hereditary cystic kidney diseases/renal ciliopathies. Issue 9 (11th September 2020) - Dahmer-Heath, Mareike; Schriever, Valentin; Kollmann, Sabine; Schleithoff, Carolin; Titieni, Andrea; Cetiner, Metin; Patzer, Ludwig; Tönshoff, Burkhard; Hansen, Matthias; Pennekamp, Petra; Gerß, Joachim; Konrad, Martin; et al.
Abstract : Background: Hereditary cystic kidney diseases such as nephronophthisis, polycystic kidney disease and Bardet-Biedl syndrome (BBS) are caused by a dysfunction of primary cilia. Cilia are involved in a variety of cellular functions and perceptions, with one of them being the sense of smell. Hyposmia is a typical feature found in patients with BBS. However, reports of olfactory dysfunction in other cystic kidney diseases are sparse. Here we provide a systematic survey on olfaction in a large cohort of patients displaying genetically determined renal ciliopathies. Methods: We performed a match-controlled systematic olfactory evaluation in a group of 75 patients with a defined genetic background using age adapted and validated odour identification tests. Results: Test results revealed a significant olfactory deficit in patients carrying TMEM67 variants (n=4), while all other genetic disorders causing nephronophthisis (n=25) or polycystic kidney disease (n=18) were not associated with an impaired sense of smell. Also in patients with BBS, olfactory performance was depending on the underlying molecular defect. While defects in the BBS1 gene (n=9) had no impact on the sense of smell, all other BBS gene disorders (n=19) were associated with significant hyposmia. Noteworthy, there was no correlation of the olfactory deficit with the level of renal impairment. Conclusion: Hyposmia is a part of the clinical spectrum of BBS and of other renal ciliopathies. Depending on the genetic background, clinicians should be aware of this subtle and so far underappreciated symptom when clinically assessing patients with BBS or TMEM67 gene variants.